Halal Certification Among the SMEs in Kinabalu, Sabah - Hasan, Haslinda; Sulong, Rini Suryati; Tanakinjal, Geoffrey Harvey (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
Halal is an important concept that enables and simplifies the consuming process of food and beverage products, especially for Muslim consumers. The study believes that the development of Halal is a communally obligatory (fardhu kifayah) for that SMEs and a personally obligatory (fardhu ain) for the Muslim consumer. The Government of Malaysia has already recognized the importance of SMEs, implemented various policies; action plans, and also introduced Halal related programs to assist the SMEs. The objectives of the study are to identify the awareness and perception towards Halal certification among SMEs in Sabah. 42 SMEs were participated in the study; the results indicated that they are aware of the role of Halal certification, and how Halal will make them competitive in the market. Majority of them are keen to become Halal certified company however the SMEs responded that to be Halal certified company the process is expensive and complicated. This paper is hoped to contribute to a better understanding of the current situation of how Halal certification can help SMEs to grow their businesses. Further study on this matter is suggested in order to gain more accurate, interesting and detailed information on the issue.